Vacuum-assisted closure therapy as adjunct to treatment of grotesque subcutaneous emphysema after blunt chest trauma: A case report - Lieb, Sebastian; Rudin, Mark; Meier, Christoph (Indian Journal of Case Reports, 2018)
Subcutaneous emphysema (SE) is a potentially life-threatening complication derived from a pneumothorax. Treatment can be challenging and on an emergency basis. A 79-year-old patient was admitted with blunt chest trauma after a motor vehicle accident. Computed tomography showed incarceration of lung parenchyma in a fractured rib without pneumothorax. The patient was initially stable, but later on developed several episodes of acute dyspnea with bilateral pneumothoraces and life-threatening SE. Further assessment using chest X-ray was complicated by SE. Treatment consisted of chest tube insertion and additional vacuum-assisted closure (VAC) therapy of the SE using a pectoral incision. Symptoms resolved quickly, and chest tube and VAC-therapy could be discontinued by day 7 and 3, respectively. Immediate chest tube insertion is the first-line treatment for trauma patients with massive SE, even if a pneumothorax may not reliably be diagnosed initially. Supportive VAC-therapy must be considered to accelerate the decline of massive SE.